MSH2, MSH6, MLH1, and PMS2 immunohistochemistry as highly sensitive screening method for DNA mismatch repair deficiency syndromes in pediatric high-grade glioma - Friker, Lea L.; Perwein, Thomas; Waha, Andreas; Dörner, Evelyn; Klein, Rebecca; Blattner-Johnson, Mirjam; Layer, Julian P.; Sturm, Dominik; Nussbaumer, Gunther; Kwiecien, Robert; Spier, Isabel; Aretz, Stefan; et al. (Acta neuropathologica, 2025)
Pediatric high-grade glioma (pedHGG) can occur as first manifestation of cancer predisposition syndromes resulting from pathogenic germline variants in the DNA mismatch repair (MMR) genes MSH2, MSH6, MLH1, and PMS2. The aim of this study was to establish a generalized screening for Lynch syndrome and constitutional MMR deficiency (CMMRD) in pedHGG patients, as the detection of MMR deficiencies (MMRD) may enable the upfront therapeutic use of checkpoint inhibitors and identification of variant carriers in the patients’ families. We prospectively enrolled 155 centrally reviewed primary pedHGG patients for MMR-immunohistochemistry (IHC) as part of the HIT-HGG-2013 trial protocol. MMR-IHC results were subsequently compared to independently collected germline sequencing data (whole exome sequencing or pan-cancer DNA panel next-generation sequencing) available in the HIT-HGG-2013, INFORM, and MNP2.0 trials. MMR-IHC could be successfully performed in 127/155 tumor tissues. The screening identified all present cases with Lynch syndrome or CMMRD (5.5%). In addition, MMR-IHC also detected cases with exclusive somatic MMR gene alterations (2.3%), including MSH2 hypermethylation as an alternative epigenetic silencing mechanism. Most of the identified pedHGG MMRD patients had no family history of MMRD, and thus, they represented index patients in their families. Cases with regular protein expression in MMR-IHC never showed evidence for MMRD in DNA sequencing. In conclusion, MMR-IHC presents a cost-effective, relatively widely available, and fast screening method for germline MMRD in pedHGG with high sensitivity (100%) and specificity (96%). Given the relatively high prevalence of previously undetected MMRD cases among pedHGG patients, we strongly recommend incorporating MMR-IHC into routine diagnostics.
Online veröffentlicht: 2. Februar 2025
Gesehen am 10.07.2025